Punctuation in L2 Italian textbooks and in Italian linguistics textbooks for secondary schools in Italy - Diadori, Pierangela (Kwartalnik Neofilologiczny, 2026)
This article is devoted to the treatment of Italian punctuation in textbooks for Italian as a second language (L2) and of Italian linguistics textbooks for secondary schools in Italy, published during the past thirty years. The aim is to understand what role punctuation plays, how it is explained, and which texts and exercises are used. The objective is to connect the findings of the most recent linguistic research with their reception in educational contexts, both within the Italian school system and in relation to the broader audience of L2 learners of Italian.